Managerial Structure of Editorship: Functions and Purposes - M. N. Kim (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
In the article the author considers collective and personalized forms of management of the editorial staff. In the author’s opinion, in the modern editions the administrative link of the edition is subject to constant changes and searches. It all depends not only on the quantitative composition of the editorial board, but also on the management tasks ahead for the leadership of the publication. What is the model of management the most preferable in modern conditions? What are administrative tasks of editorial management? What functional roles do they play? These are the primary issues that the author tried to answer in this article. The primary research objective of this project is the determine the main functions of collegial and personalized subjects of management, on which the success of the editorial team mainly depends. In the modern edition, management functions can be performed collegial bodies (editorial board, secretariat) as well as by personalized persons (editor-in-chief, Executive Secretary, etc.). They can perform their regulatory functions through the principles of directive, regulation and normativity. The author appeals to the analysis of domestic media experience in the field of editorial management, to show how these principles are put into practice.